Biotic interactions mediate soil microbial feedbacks to climate change - Crowther, Thomas W. (Proc Natl Acad Sci U S A, 2015)
Decomposition of organic material by soil microbes generates an annual global release of 50–75 Pg carbon to the atmosphere, ∼7.5–9 times that of anthropogenic emissions worldwide. This process is sensitive to global change factors, which can drive carbon cycle–climate feedbacks with the potential to enhance atmospheric warming. Although the effects of interacting global change factors on soil microbial activity have been a widespread ecological focus, the regulatory effects of interspecific interactions are rarely considered in climate feedback studies. We explore the potential of soil animals to mediate microbial responses to warming and nitrogen enrichment within a long-term, field-based global change study. The combination of global change factors alleviated the bottom-up limitations on fungal growth, stimulating enzyme production and decomposition rates in the absence of soil animals. However, increased fungal biomass also stimulated consumption rates by soil invertebrates, restoring microbial process rates to levels observed under ambient conditions. Our results support the contemporary theory that top-down control in soil food webs is apparent only in the absence of bottom-up limitation. As such, when global change factors alleviate the bottom-up limitations on microbial activity, top-down control becomes an increasingly important regulatory force with the capacity to dampen the strength of positive carbon cycle–climate feedbacks.